2008
DOI: 10.2340/16501977-0129
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance training after stroke: Effects on muscle strength, muscle tone, gait performance and perceived participation

Abstract: Objective: To evaluate the effects of progressive resistance training on muscle strength, muscle tone, gait performance and perceived participation after stroke. Design: A randomized controlled trial. Subjects: Twenty-four subjects (mean age 61 years (standard deviation 5)) 6-48 months post-stroke. Methods: The training group (n = 15) participated in supervised progressive resistance training of the knee muscles (80% of maximum) twice weekly for 10 weeks, and the control group (n = 9) continued their usual dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 31 publications
7
118
0
9
Order By: Relevance
“…4 Ten weeks of progressive resistance training (PRT; 80% of 1 Repetition Maximum) after stroke significantly improved knee muscle strength (+14% to +73%) as well as gait performance (+10% to +19%), without any negative effects on muscle tone. 26 When comparing these two interventions, the magnitude of the improvements was much larger after PRT than after WBV training in individuals with chronic stroke.…”
Section: Discussionmentioning
confidence: 96%
“…4 Ten weeks of progressive resistance training (PRT; 80% of 1 Repetition Maximum) after stroke significantly improved knee muscle strength (+14% to +73%) as well as gait performance (+10% to +19%), without any negative effects on muscle tone. 26 When comparing these two interventions, the magnitude of the improvements was much larger after PRT than after WBV training in individuals with chronic stroke.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, various interventions, such as neurodevelopmental treatment (Graham et al 2009), task-oriented training (Leroux et al 2006), and progressive resistance training (Flansbjer et al 2008) have been devised to improve the balancing ability in stroke patients. However, traditional balance training schemes rely on the repetition of specific movements, which many patients find aimless and boring, resulting in reduced motivation and compliance with training programs (Gil-Gomez et al 2011).…”
mentioning
confidence: 99%
“…I n c o n t r a s t , w h i l e p r e v i o u s s t u d i e s r e p o r t e d improvements ranging from 18% to 54% for knee extensors or flexors 35) , the results of the present study showed improvements in 1RM (36.4%) generated by the major muscle groups of the lower extremity, despite the lower frequency and intensity of our study protocol. In general, previous studies have supported the contention that the muscle weakness observed in chronic stroke subjects can be modified through appropriate exercise 28,36,37) . The performance of normal movement requires the ability to execute alternating movements at various functional speeds, while maintaining appropriate timing between antagonist muscle groups.…”
Section: Discussionmentioning
confidence: 69%